El derecho romano de la propiedad en la doctrina civil colombiana - Escobar Córdoba, Federico (2023)
This article shows how legal writers in Colombia have frequently adopted the idea that Roman jurists conceived of three divisions within the right of ownership, called usus, fructus, and abusus. The text then turns to primary sources of Roman Law, and shows that this concept was not theorized by Roman jurists. The analysis continues with secondary sources of Roman Law, underscoring the fact that Colombian authors commonly describe this triple division as a Roman creation, while foreign legal writers on Roman Law generally do not. The article concludes by suggesting that this is one case of what the author calls “blind spots,” referring to the way in which members of the legal community tend to reproduce certain traditional ideas without seeing their real content or origin.